The concept of law : a comparative study of the Shari'ah concept of hukm with various relevant theories of law in western jurisprudence - Saad, Abu Elgasim Saad (Ahmad Ibrahim Kulliyyah of Laws,International Islamic University Malaysia, 2013)
For an appropriate concept of law to be developed, an appropriate dual relation has to be formulated between law and ethics on one hand, and law and the state on the other. The formulation of such an appropriate dual relation accounts for the three aspects involved by law as a social phenomenon, namely, the ethical, social and political. Interestingly, the development of a concept of law as a consequence of the formulation of the dual relation just mentioned results in the recognition of a concept wider than the concept of law of which the concept of law is only a derivative and in terms of which the concept of law is necessarily intelligible. Fortunately, this concept is believed to be the concept of hukm already existing in Islamic jurisprudence, nevertheless it cannot be said to be perfect. On the other hand, the concept of law supposed to be derived from it does not exist or, in other words, the perspective from which it is addressed is an individual-based that does not stress the distinguishing line between law and hukm. On the contrary, the concept of hukm in Western jurisprudence does not exist, and because of that the various Western approaches to the concept of law are defective. In light of the aforementioned background, this study seeks to achieve the following objectives: First, to introduce a slightly modified version of the Shari'ah concept of hukm in Islamic jurisprudence. Second, to synthesize a concept of hukm in Western jurisprudence distinguishable from the concept of law and modelled on the concept of hukm in Islamic jurisprudence. Third, to synthesize an institution-based concept of law in Islamic jurisprudence that is distinguishable from the concept of hukm and articulated along the analytical lines drawn in Western jurisprudence. Fourth, to criticize the defective approaches to the concept of law in Western jurisprudence so as to reconstruct them in the way the concept of law is constructed in Islamic jurisprudence. This descriptive, analytical and critical comparative library-based study of the concept of law in both Islamic jurisprudence and Western jurisprudence is a qualitative research that follows an inductive and deductive methodology in order to achieve its objectives. It follows an inductive methodology in the sense that it reviews the relevant literature in both schools of jurisprudence so as to identify how law is seen and conceptualized. Such an inductive methodology is reflected in the descriptive approach to the literature reviewed. It also follows a deductive methodology in the sense that it subjects the literature reviewed to an analytical and critical treatment so as to figure out the true characteristic features of the phenomenon intended to be designated, viz. law. Having followed the aforementioned methodology, the study has arrived at the conclusion that law is a coercive institutional subset of standards that belongs to a wider set that is ethical in nature. This subset of standards has been institutionalized by the state responsible for its creation and application in order to protect it by its coercive power. The state's creation and application of the law takes place by virtue of paying obedience to the value system to which the law created and applied belongs. Law, then, is a political regulatory system that is subordinate and subservient to an ethical regulatory system. What accounts for the subordination and subservience of the law to the ethical system is the concept of hukm and not the concept of law. In other words, what accounts for the creation and application of the law is the concept of hukm and not the concept of law whereby it could be asserted that if law is to be appropriately designated and interpreted, the task of elucidating it has to be shifted from the concept of law to the concept of hukm